Pemanfaatan Teknologi Laser Cutting Dalam Proses Perancangan Perhiasan Berbahan Akrilik Lembaran Dengan Pendekatan Eksplorasi Bentuk - Meryam Nur Putri; Dedy Ismail (Aliansi Desainer Produk Industri Indonesia (ADPII), 2020)
Acrylic material has unique characteristics to be made into a jewelry material with variety shapes and colors that has been available in the market. Many jewelry industries has been using acrylic as their main material to make a jewelry by using a variety of modules (beads) which are numerous in the market. The dependence of modules in the market makes a lot of jewelry industries using an acrylic, that relies to their relation to develop in the market. An opportunity to develop acrylic jewelry by using laser cutting technology in the creative process (design) and then developed into new modules. The shape exploration is very precisely to develop jewelry designs with a new variety modules, and makes designers not put their dependency on the modules in the market.